Teaching worldviews through creative drama for religious education in Turkey - Tosun, Aybiçe (International journal of children's spirituality, 2018)
Over the last two decades, Worldview Approach has been mentioned in the field of religious education and spirituality. This article aims to determine the effects of creative drama on teaching worldviews and religions. The main purpose of Worldview Education is to assist individuals to have a broader and deeper understanding on self-identity, worldviews of others, and on the meaning and purpose of life. It also helps individuals to think on ontological, epistemological and ultimate questions about life, values and beliefs. The spiritual development of individuals has a need for several guidelines from the fields of philosophy, theology, and education. As an educational tool, creative drama increases imagination, creativity, problem-solving and critical thinking skills and assists students' personal and emotional development. Combining Worldview Education with creative drama creates a multidimensional educational environment for a meaningful learning on religions, worldviews, and spirituality.